Role of Nintedanib in COVID-19-Related Lung Fibrosis - Alif Fathurrachman; Linda Andriani; Rouly Pasaribu; Sudarto Sudarto; Ahmad Rasyid; Zen Ahmad; Tommy Setiawan (Faculty of Medicine Universitas Airlangga, 2022)
In December 2020, Indonesia was introduced to the long Coronavirus disease 2019 (COVID-19) phenomenon. The Centers for Disease Control and Prevention (CDC) introduced the term